Lime-induced phytophotodermatitis - Andrew Hankinson; Benjamin Lloyd; Richard Alweis (Greater Baltimore Medical Center, 2014)
This case describes a scenario of lime-induced phytophotodermatitis. Phytophotodermatitis is a dermatitis caused after the skin is exposed to photosensitizing compounds in plants and then exposed to sunlight. Many common plants including citrus fruits, celery, and wild parsnip contain these photosensitizing compounds which cause phytophotodermatitis. It is important for a physician to be aware of phytophotodermatitis because it may often be misdiagnosed as other skin conditions including fungal infection, cellulitis, allergic contact dermatitis, and even child abuse.